Impact of RNase E and RNase J on Global mRNA Metabolism in the Cyanobacterium Synechocystis PCC6803 - Cavaiuolo, Marina; Chagneau, Carine; Laalami, Soumaya; Putzer, Harald (Frontiers in Microbiology, 2020)
mRNA levels result from an equilibrium between transcription and degradation. Ribonucleases (RNases) facilitate the turnover of mRNA, which is an important way of controlling gene expression, allowing the cells to adjust transcript levels to a changing environment. In contrast to the heterotrophic model bacteria Escherichia coli and Bacillus subtilis, RNA decay has not been studied in detail in cyanobacteria. Synechocystis sp. PCC6803 encodes orthologs of both E. coli and B. subtilis RNases, including RNase E and RNase J, respectively. We show that in vitro Sy RNases E and J have an endonucleolytic cleavage specificity that is very similar between them and also compared to orthologous enzymes from E. coli, B. subtilis and Chlamydomonas. Moreover, Sy RNase J displays a robust 5’-exoribonuclease activity similar to B. subtilis RNase J1, but unlike the evolutionarily related RNase J in chloroplasts. Both nucleases are essential and gene deletions could not be fully segregated in Synechocystis. We generated partially disrupted strains of Sy RNase E and J that were stable enough to allow for their growth and characterization. A transcriptome analysis of these strains partially depleted for RNases E and J, respectively, allowed to observe effects on specific transcripts. RNase E altered the expression of a larger number of chromosomal genes and antisense RNAs compared to RNase J, which rather affects endogenous plasmid encoded transcripts. Our results provide the first description of the main transcriptomic changes induced by the partial depletion of two essential ribonucleases in cyanobacteria.